An alternative CTCF isoform antagonizes canonical CTCF occupancy and changes chromatin architecture to promote apoptosis - Li, Jiao; Huang, Kaimeng; Hu, Gongcheng; Babarinde, Isaac A.; Li, Yaoyi; Dong, Xiaotao; Chen, Yu-Sheng; Shang, Liping; Guo, Wenjing; Wang, Junwei; Chen, Zhaoming; Hutchins, Andrew P.; et al. (Nature communications, 2019)
CTCF plays key roles in gene regulation, chromatin insulation, imprinting, X chromosome inactivation and organizing the higher-order chromatin architecture of mammalian genomes. Previous studies have mainly focused on the roles of the canonical CTCF isoform. Here, we explore the functions of an alternatively spliced human CTCF isoform in which exons 3 and 4 are skipped, producing a shorter isoform (CTCF-s). Functionally, we find that CTCF-s competes with the genome binding of canonical CTCF and binds a similar DNA sequence. CTCF-s binding disrupts CTCF/cohesin binding, alters CTCF-mediated chromatin looping and promotes the activation of IFI6 that leads to apoptosis. This effect is caused by an abnormal long-range interaction at the IFI6 enhancer and promoter. Taken together, this study reveals a non-canonical function for CTCF-s that antagonizes the genomic binding of canonical CTCF and cohesin, and that modulates chromatin looping and causes apoptosis by stimulating IFI6 expression. CTCF plays key roles in gene regulation, chromatin insulation and organizing the higher-order chromatin architecture of mammalian genomes. Here the authors investigate the function an alternatively spliced shorter CTCF isoform, finding that this isoform antagonizes canonical CTCF occupancy and changes chromatin architecture to promote apoptosis.